Advances in pavement design through full-scale accelerated pavement testing proceedings of the 4th International Conference on Accelerated Pavement Testing, Davis, CA, USA, 19-21 September 2012 - Jones, David; Harvey, John (John T.); Mateos, Angel; Al-Qadi, Imad L. (CRC Press /Balkema, 2012)
Advances in Pavement Design through Full-scale Accelerated Pavement Testing will be useful to academics and professionals involved in pavement engineering